Integrating rhythmic syllable with tonguing drills in elementary brass instruments instruction - Khor, A. K.; Chan, C. J.; Roslan, Samsilah (Universiti Putra Malaysia Press, 2016)
Various rhythm syllable systems that are based on the concept that prioritises ‘sound before symbol’ are known to be able to enhance students’ ability to read music notations. To date, these systems are yet to be integrated with basic brass instrumental skills such as tonguing. This research examines the effect of the rhythm syllable system when it is applied as an integrated teaching approach for novice brass instrument learners by combining rhythm learning with articulation. A teaching experiment was conducted with 90 elementary trumpet students assigned randomly into three groups. Each group underwent five weeks of intervention with a single content but using different approaches of rhythm learning. Data analysis showed significant differences among the groups, and the group that used the adapted rhythmic syllable approach achieved the highest both in rhythm accuracy and articulation clarity, followed by the group that used Kodaly syllables and the control group that did not apply any particular syllable system. The integrated rhythmic syllable reduces the time of learning the brass instrument while eliminating the redundancies resulting from compartmentalised teaching. This research has extended the scope of application of the rhythmic syllable system beyond musicianship training. It indicates that methods in musicianship training can be localised for specific purposes in instrumental learning.